Sistem Pakar untuk Diagnosis Penyakit Ayam menggunakan Metode Certainty Factor (Studi Kasus: Balai Besar Pelatihan Peternakan Batu) - Ishak Panangian Sinaga; Arief Andy Soebroto; Imam Cholissodin (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Chickens are livestock that are mostly kept by the people of Indonesia, both kept in small quantities to large numbers which are developed in large-scale chicken farms. The choice of people to choose to raise chickens is none other than due to easy maintenance, high public consumption, so that raising chickens is a promising source of income. However, chicken farming itself is very at risk of experiencing a cycle of losses as happened in 2020 where there is a mass transmission of chicken diseases. This mass transmission of chicken disease occurs due to various factors. To overcome this problem, chicken farmers usually consult with experts but for this sector the number of experts is still small so the community really needs the presence of experts to help deal with this problem. To solve this problem, an expert system for diagnosis of chicken disease was built where the expert system is a computer program designed to model the problem solving ability of an expert. The application of this expert system will make it easier for chicken farmers to diagnose disease and treat the same as experts. This expert system is implemented with the Certainty Factor method where this method will provide as accurate results as possible because the certainty value obtained from the expert will always be maintained stable due to calculations To find the certainty value, only two data are used. The application of the Certainty Factor method to the expert system has several stages, from getting the MB and MD values, performing operations according to the Certainty Factor equation to get the CF value and to get the combined CF value using the combined CF equation.